Keep in step with the Spirit - Packer, James Innell, 1926- (Old Tappan, NJ Fleming H. Revell, 1984)
Includes bibliographical references and indexes.
Keywords: Holy Spirit; Spritual life; Gifts, spiritual; Sanctification